Simultaneous Detection of Pathogens and Tumors in Patients With Suspected Infections by Next-Generation Sequencing - Su, Jiachun; Han, Xu; Xu, Xiaogang; Ding, Wenchao; Li, Ming; Wang, Weiqin; Tian, Mi; Chen, Xiyuan; Xu, Binbin; Chen, Zhongqing; Yuan, Jinyi; Qin, Xiaohua; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Differential diagnosis of patients with suspected infections is particularly difficult, but necessary for prompt diagnosis and rational use of antibiotics. A substantial proportion of these patients have non-infectious diseases that include malignant tumors. Methods: Based upon Metagenomic next-generation sequencing (mNGS) technologies and chromosomal copy number variation (CNV) analysis on abundant human genome, a new procedure named Onco-mNGS was established to simultaneously detect pathogens and malignant tumors in patients with suspected infections. Results: Of 140 patients screened by Onco-mNGS testing at four hospitals in Shanghai, 115 patients were diagnosed with infections; 17 had obvious abnormal CNV signals indicating malignant tumors that were confirmed clinically. The sensitivity and specificity of mNGS testing for diagnosis of a clinically relevant infection was 53.0% (61/115) and 60% (15/25), respectively, vs 20.9% (24/115) and 96.0% (24/25), respectively, for conventional microbiological testing (both P<0.01). Klebsiella pneumoniae was the most common pathogen detected by mNGS, followed by E. coli and viruses. The chromosomal abnormalities of the 17 cases included genome-wide variations and local variations of a certain chromosome. Five of 17 patients had a final confirmed with malignant tumors, including three lung adenocarcinomas and two hematological tumors; one patient was highly suspected to have lymphoma; and 11 patients had a prior history of malignant tumor. Conclusion: This preliminary study demonstrates the feasibility and clinical value of using Onco-mNGS to simultaneously search for potential pathogens and malignant tumors in patients with suspected infections.